Transcriptional and Physiological Responses of Genes Related to Nutrient Uptakes and Toxin Production of Alexandrium minutum (Dinophyceae) in Malaysia Waters - Hii, Kieng Soon (Universiti Malaysia Sarawak (UNIMAS), 2017)
Saxitoxins (STXs) is a family of potent sodium channel blocking toxins, also causative agents of paralytic shellfish poisoning (PSP) that is produced by several species of marine dinoflagellates and cyanobacteria. Two STX-core genes (sxt), sxtA and sxtG have been well elucidated in Alexandrium but the expression of these genes under various nutritional modes in tropical species remained unclear. The nutrient fluxes and the bloom of Alexandrium have also been intensively studied but the genetically nutrient regulation mechanisms in nutrient uptakes on this genus are still unknown. This study aims to investigate the physiological responses of the tropical Pacific strains of A. minutum in nitrate- or ammonium-grown culture conditions, and with various nitrogen to phosphorus supply ratios (N:P). The transcriptional responses of the sxt, nutrient transporters and assimilation genes were observed. Likewise, a putative sxtI encoding Ocarbamoyltransferase (herein designated as AmsxtI) was recovered from the transcriptomic data, and the relative expression was investigated. The results have revealed that the cellular toxin quota (Qt) was higher in P-deficient nitrate-grown cultures. Between cultures grown at similar N: P (<16), cells grown in excess ammonium showed higher Qt than that of the nitrate-grown cultures. sxtA1 was not expressed in the culture conditions suggesting that the gene might not be involved in STX biosynthesis of this strain. Conversely, sxtA4 and sxtG showed positive correlations with Qt, and up-regulated at P-deficient nitrategrown cultures and excess ammonium environment. On the other hand, relative expression of AmsxtI was induced only at P-deficient environment suggesting that it may play an important role in the P-recycling metabolism and simultaneously enhances the toxin production. Conversely, the A. minutum novel high affinity nitrate, ammonium and phosphate transporter genes (AmNrt2, AmAmt1 and AmPiPT1); as well as assimilation genes, cytosol nitrate reductase (AmNas), mitochondria glutamine syntheses (AmGSIII) and pyrimidine syntheses carbamoyl phosphate syntheses (AmCPSII) were assembled by the Sequence Read Archive (SRA) dataset. AmAmt1 was suppressed in excess ammoniumgrown, but not for AmNrt2 and AmNas, suggesting that the nitrate uptake was preferred in this species. AmAmt1, AmNrt2, AmNas, AmGSIII, AmCPSII and AmPiPT1 were highly expressed in P-deficient environment showing that A. minutum is likely to be able to take up nutrients for growth under P-stress condition. Relative expression of AmCPSII was incongruent with the cells growth, but it was well correlated with Qt, postulating that the gene might involve in arginine metabolism and concurrently related to toxin production. Besides that, the AmGSIII expression in this study has found that the SXT production of the cells also is a manner to detoxify or release excess ammonium environment stress. The gene regulation of this study has provided better insights into the eco-physiology of A. minutum in relation to the toxin production and its adaptative strategies in the unfavourable environment. This will be an advantageous for the future harmful algae blooms (HABs) monitoring.